The Designing of a Digital Book on the History of Rubber Plantation Based on the Experiential Learning Model as a Trigger for Learning History Meaning Entrepreneurship - Monalisa monalisa; Muhammad Akhyar; Musa Pelu (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: To achieve the level of prosperity is not an easy thing. Becoming an entrepreneur is not an alternative profession, but being an entrepreneur is a strategic choice that must be made with a firm and strong determination. Findings: The essence of entrepreneurship is to build an entrepreneurial atmosphere so that students like challenges, are creative, innovative, and have the courage to take or manage risks (character). Research limitations/implications: Imagine if all graduates in Indonesia had entrepreneurial characters, of course Indonesia would rise to become an authoritative country in the eyes of the world. Indonesia will have strong competitiveness, its economy will be independent, and its image will improve. Practical implications: The formulation of the problem in this study is how the entrepreneurial attitude of students so far and how the needs of teachers and students for teaching materials that can improve the entrepreneurial attitude of students. Paper type: Research paper.